2014
DOI: 10.1007/s11033-014-3038-4
|View full text |Cite
|
Sign up to set email alerts
|

Primordial follicle assembly was regulated by notch signaling pathway in the mice

Abstract: Notch signaling pathway, a highly conserved cell signaling system, exists in most multicellular organisms. The objective of this study was to examine Notch signaling pathway in germ cell cyst breakdown and primordial follicle formation. The receptor and ligand genes of Notch pathway (Notch1, Notch2, Jagged1, Jagged2 and Hes1) were extremely down-regulated after newborn mouse ovaries were cultured then exposed to DAPT or L-685,458 in vitro (P < 0.01). Since DAPT or L-685,548 inhibits Notch signaling pathway, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Therefore, in the present study, we observed two critical periods during the formation and transformation of primordial follicles. Early studies found that Notch signaling mediates primordial follicle formation and transformation, particularly involving the SOHLH2, NOBOX and LHX8 transcription factors [26,27]. Early studies found that downregulation of mRNA expression of sohlh2 , nobox and lhx 8 alters primordial follicle numbers and results in a lifelong reduction in the primordial follicle pool [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study, we observed two critical periods during the formation and transformation of primordial follicles. Early studies found that Notch signaling mediates primordial follicle formation and transformation, particularly involving the SOHLH2, NOBOX and LHX8 transcription factors [26,27]. Early studies found that downregulation of mRNA expression of sohlh2 , nobox and lhx 8 alters primordial follicle numbers and results in a lifelong reduction in the primordial follicle pool [26].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that Notch signaling mediates primordial follicle formation and transformation, particularly involving the SOHLH2, NOBOX and LHX8 transcription factors [26,27]. Early studies found that downregulation of mRNA expression of sohlh2 , nobox and lhx 8 alters primordial follicle numbers and results in a lifelong reduction in the primordial follicle pool [26]. Interestingly, in the present study, we did not observe a difference in the gene expression level of sohlh2 , nobox and lhx 8 in the fetal ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study reported rodent ovary culture has been successfully performed by other investigators to confirm roles for signaling molecules during early follicle formation [24,27,52]. We utilize an in vivo follicle formation model in this system, arguing that factors important for follicle assembly are important to ovarian development.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Hippo signaling pathway, which consists of several oncogenes (MST1/LATS2/YAP1)could sense the changes of cell density in Drosophila ovaries [22]. The Hippo signaling pathway forms a cross network with a variety of factors and multiple signaling pathways such as Notch, TGFβ, cTGF, IGF, c-erbB2, c-myc, and PI3K/AKt in different levels [23,24,25,26,27]. Our earlier reports demonstrated that the physiological effect of Pten and Tsc1/mTorc1 signaling pathways, which have been proved to maintain of the quiescence of primordial follicles, included anti-oncogenes that activated in the course of tumorigenesis [28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the culturing, the ovarian tissues were collected and washed three times with PBS for the indicated analyses. Oocytes were isolated from the cultured ovarian tissues as previously described [23][24][25][26][27].…”
Section: Ovarian Culturementioning
confidence: 99%